Pan-genomic and transcriptomic analyses of Leuconostoc mesenteroides provide insights into its genomic and metabolic features and roles in kimchi fermentation - Chun, Byung Hee; Kim, Kyung Hyun; Jeon, Hye Hee; Lee, Se Hee; Jeon, Che Ok (Scientific Reports, 2017)
The genomic and metabolic features of Leuconostoc (Leu) mesenteroides were investigated through pan-genomic and transcriptomic analyses. Relatedness analysis of 17 Leu. mesenteroides strains available in GenBank based on 16S rRNA gene sequence, average nucleotide identity, in silico DNA-DNA hybridization, molecular phenotype, and core-genome indicated that Leu. mesenteroides has been separated into different phylogenetic lineages. Pan-genome of Leu. mesenteroides strains, consisting of 999 genes in core-genome, 1,432 genes in accessory-genome, and 754 genes in unique genome, and their COG and KEGG analyses showed that Leu. mesenteroides harbors strain-specifically diverse metabolisms, probably representing high evolutionary genome changes. The reconstruction of fermentative metabolic pathways for Leu. mesenteroides strains showed that Leu. mesenteroides produces various metabolites such as lactate, ethanol, acetate, CO2, mannitol, diacetyl, acetoin, and 2,3-butanediol through an obligate heterolactic fermentation from various carbohydrates. Fermentative metabolic features of Leu. mesenteroides during kimchi fermentation were investigated through transcriptional analyses for the KEGG pathways and reconstructed metabolic pathways of Leu. mesenteroides using kimchi metatranscriptomic data. This was the first study to investigate the genomic and metabolic features of Leu. mesenteroides through pan-genomic and metatranscriptomic analyses, and may provide insights into its genomic and metabolic features and a better understanding of kimchi fermentations by Leu. mesenteroides.